Pemanfaatan Tanaman Herbal sebagai Alternatif dalam Pengobatan Hipertensi di Desa Mersam Kabupaten Batang Hari - Agung As’adi, M.Henityo; Nabhaki, Firelza; Ripani, Izani Fathya; Arista, Dina; Susanti, Siti Melvy; Lestari, Wiwik; Wahyuni, Intan Sri; Sandy, Sapna Ari; Hayeti, Triana Najma; Prianggie, Sherly Alensia (Universitas Baiturrahim, 2025)
One type of community service is Real Work Lectures (KKN), which aims to apply knowledge and skills in social life. In Mersam Village, Mersam District, Batanghari Regency, Jambi, there is a real work program with the theme